Genomics and proteomics approaches to the study of cancer-stroma interactions - Rodrigues-Lisoni, Flavia C. [UNESP]; Peitl, Paulo [UNESP]; Vidotto, Alessandra; Polachini, Giovana M.; Maniglia, Jose V.; Carmona-Raphe, Juliana; Cunha, Bianca R.; Henrique, Tiago; Souza, Caique F.; Teixeira, Rodrigo A. P. [UNESP]; Fukuyama, Erica E.; Michaluart, Pedro; et al. (Biomed Central Ltd., 2010)
Background: The development and progression of cancer depend on its genetic characteristics as well as on the interactions with its microenvironment. Understanding these interactions may contribute to diagnostic and prognostic evaluations and to the development of new cancer therapies. Aiming to investigate potential mechanisms by which the tumor microenvironment might contribute to a cancer phenotype, we evaluated soluble paracrine factors produced by stromal and neoplastic cells which may influence proliferation and gene and protein expression.Methods: The study was carried out on the epithelial cancer cell line (Hep-2) and fibroblasts isolated from a primary oral cancer. We combined a conditioned-medium technique with subtraction hybridization approach, quantitative PCR and proteomics, in order to evaluate gene and protein expression influenced by soluble paracrine factors produced by stromal and neoplastic cells.Results: We observed that conditioned medium from fibroblast cultures (FCM) inhibited proliferation and induced apoptosis in Hep-2 cells. In neoplastic cells, 41 genes and 5 proteins exhibited changes in expression levels in response to FCM and, in fibroblasts, 17 genes and 2 proteins showed down-regulation in response to conditioned medium from Hep-2 cells (HCM). Nine genes were selected and the expression results of 6 down-regulated genes (ARID4A, CALR, GNB2L1, RNF10, SQSTM1, USP9X) were validated by real time PCR.Conclusions: A significant and common denominator in the results was the potential induction of signaling changes associated with immune or inflammatory response in the absence of a specific protein.